Performance, electrochemical process analysis and degradation of gadolinium doped ceria as fuel electrode material for solid oxide electrolysis cells. (1st June 2023) - Uecker, Jan; Unachukwu, Ifeanyichukwu D.; Vibhu, Vaibhav; Vinke, Izaak C.; Eichel, Rüdiger-A.; (Bert) de Haart, L.G.J.
Highlights: Steam- and co-electrolysis using a single cell containing a GDC fuel electrode. A current density of -914 mA‧cm −2 in steam electrolysis (1.5 V, 900 °C). 70% of the performance of Ni-GDC fuel electrode single cells. Degradation rate of 112 mV‧kh -1 ; which is four times lower than Ni-GDC. GDC fuel electrode does not significantly contribute to the degradation. Abstract: One major challenge that has to be solved to enable a market entry of solid oxide electrolysis cells (SOECs) technology is the poor degradation behaviour caused by nickel agglomeration and migration in the state-of-the-art fuel electrodes. Novel fuel electrode materials that either suppress the nickel migration or even nickel-free electrodes could lead to a decrease in degradation rates. In this work, single cells based on the mixed ionic electronic conducting (MIEC) gadolinium doped ceria (GDC), acting as single-phase fuel electrode, were prepared. The cell performance was investigated by current density-voltage characteristics (jV) for steam and co-electrolysis conditions at various operating temperatures. Furthermore, electrochemical processes occurring in the single cells were analysed using electrochemical impedance spectroscopy (EIS), distribution of relaxation times (DRT) analysis and equivalent circuit model (ECM) fitting. Current densities of –914 and –969 mA‧cm −2, respectively, at 1.5 V and 900 °C operating temperature for steam and co-electrolysis were obtained, which corresponds to about 70% of the current density achieved in similar produced Ni-GDC fuel electrode cells. In addition, a long-term stability test was carried out during steam electrolysis (50% H2 O + 50% H2 ) at 900 °C with a constant current load of –0.5 A‧cm −2 for 1070 h. In comparison to Ni-YSZ and Ni-GDC fuel electrode single cells reported in the literature, a significantly lower degradation rate of 112 mV‧kh −1 was observed. The electrochemical investigations and post-test analyses using SEM-EDX reveal that the GDC fuel electrode does not contribute significantly to the degradation, while the LSCF oxygen electrode is the major contributor to the cells' degradation.